Salt-Related Knowledge, Attitudes and Behavior in an Intervention to Reduce Added Salt When Cooking in a Sample of Adults in Portugal - Santos, T. (2022)
(1) Background: Excessive salt intake is associated with an increased risk of hypertension and cardiovascular disease, so reducing it is critical. The main objective of this study was to verify whether one intervention to reduce added salt during cooking changed knowledge, attitudes and behavior (KAB) towards salt, and to analyze changes in the main sources of salt. (2) Methods: The intervention study was an 8-week randomized controlled trial with 97 workers from a public university. KAB in relation to salt were obtained through the WHO STEPwise questionnaire, and the main sources of salt were obtained by 24-h food recall and 24 h urinary sodium excretion over two days. (3) Results: After the intervention, participants in the intervention group reported a decrease in the addition of salt when cooking (p = 0.037), an increase in the percentage of subjects who avoided the consumption of processed foods (from 54.2% to 83.3%, p = 0.001), who looked for salt on food labels (from 18.8% to 39.6%, p = 0.013), and who bought low-salt food alternatives (from 43.8% to 60.4%, p = 0.039). However, there were no significant differences between the intervention group and the control group at baseline and post-intervention assessments. In the intervention group, after the intervention, the added salt decreased by 5%; food sources of salt such as the snacks and pizza group decreased by 7%, and the meat, fish and eggs group increased by 4%, but without statistical significance. (4) Conclusions: With innovative equipment for dosing salt when cooking, it is possible to change some dimensions of consumer behavior in relation to salt.